MOTIVASI PEMUSTAKA TERHADAP PEMAKAIAN BUKU DI PERPUSTAKAAN SMA NEGERI 1 LAMBANDIA - Marliati Thomas (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2017)
The purpose of this study is to determine the Motivation of Book Users in Library Usage in SMA Negeri 1 Lambandia in improving motivation pemustaka. The results of this study indicate that the Motivation of User Against Book Usage in the Library of SMA Negeri 1 Lambandia that the Effective Service Quality is determined by Three Standing Needs: Existence, Relatedness, and Development (Growth). The three human needs are stratified according to Alderfer's motivation has not fully run perfectly in the main development (Growth). This research is expected to provide benefits and donations of Science for Readers and Librarians that exist in the Library of SMA Negeri 1 Lambandia. This research is also expected to provide benefits in the development of Library Science, especially in the Motivational Research Against Book Usage in the Library of SMA Negeri 1 Lambandia.  Keywords: Motivation, Reader, Book Use.